The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1016/j.jpsychires.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of suicidal ideation in depressed older adults undergoing antidepressant treatment

Abstract: Suicide is a public health concern in older adults. Recent cross sectional studies suggest that impairments in executive functioning, memory and attention are associated with suicidal ideation in older adults. It is unknown whether these neuropsychological features predict persistent suicidal ideation. We analyzed data from 468 individuals ≥ age 60 with major depression who received venlafaxine XR monotherapy for up to 16 weeks. We used latent class growth modeling to classify groups of individuals based on tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
2
14
1
Order By: Relevance
“…Likewise, our findings deviate from Gujral et al (2013) who found increased global deficits and executive deficits in elderly who had attempted suicide and serious suicidal ideators (those who endorsed suicidal ideation and plan). Last, we did not find statistical associations on cognitive measures despite a recent trajectory analysis by Kasckow et al (2015) reporting that deficits in global cognitive function, attention and executive function were predictors of membership in a "high and persistent suicidal ideation trajectory". We posit that the failure to find statistical differences on cognitive variables between TESI and non-TESI group may be attributed to the low severity of suicidal ideation in our sample, the fact that these were outpatients as opposed to inpatients (as in studies by Richard-Devantoy and Gujral) and the low number of TESI participants.…”
Section: Discussioncontrasting
confidence: 89%
“…Likewise, our findings deviate from Gujral et al (2013) who found increased global deficits and executive deficits in elderly who had attempted suicide and serious suicidal ideators (those who endorsed suicidal ideation and plan). Last, we did not find statistical associations on cognitive measures despite a recent trajectory analysis by Kasckow et al (2015) reporting that deficits in global cognitive function, attention and executive function were predictors of membership in a "high and persistent suicidal ideation trajectory". We posit that the failure to find statistical differences on cognitive variables between TESI and non-TESI group may be attributed to the low severity of suicidal ideation in our sample, the fact that these were outpatients as opposed to inpatients (as in studies by Richard-Devantoy and Gujral) and the low number of TESI participants.…”
Section: Discussioncontrasting
confidence: 89%
“…While fit statistics for the GMMs identified a 2‐class solution for depressive symptoms and suicidal ideation, 3–4 class solutions are more frequently reported in the literature, based on a review of long term trajectories of depressive symptoms (Musliner et al., ) and recent studies reporting trajectories of suicidal ideation (Allan, Gros, Lancaster, Saulnier, & Stecker, ; Kasckow et al., ; Köhler‐Forsberg et al., ; Madsen et al., ,b). This discrepancy in research findings may be explained by factors such as differences in measures used to assess symptoms, differences in follow‐up periods, differences in study design (e.g., observational studies vs. trials, and variable eligibility criteria), and differences in target populations (e.g., clinical vs. population samples).…”
Section: Discussionmentioning
confidence: 99%
“…If a causal relationship between depression and suicidal thinking exists, it would be expected that individuals who experience decreases in depressive symptoms would also have decreasing suicidal thoughts, and vice‐versa, such that the measures would be tethered over time. There has been an increasing interest in analyzing longitudinal trajectories of mental health symptoms to identify subgroups with distinctive patterns of symptoms, including depressive symptoms (see Musliner, Munk‐Olsen, Eaton, & Zandi, ) and suicidal thoughts (e.g., Kasckow et al., ; Madsen, Karstoft, Secher, Austin, & Nordentoft, ; Madsen, van Spijker, Karstoft, Nordentoft, & Kerkhof, ). However, we are not aware of studies that have analyzed these factors together to examine whether tethering occurs.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only a few studies have examined prototypical trajectories of SI based on individual variation in frequency and course of SI over time. These studies have been carried out in certain predefined subsamples, such as psychiatric patient samples [ 4 , 9 - 12 ] or in teenage samples [ 13 - 16 ]. Hence, little is known about the individual variation of SI in the adult general population over time.…”
Section: Introductionmentioning
confidence: 99%